ANALYSIS OF CYANIDE ACID (HCN), CRUDE PROTEIN AND GROSS ENERGY CONTENT IN WINPROB (OTW_PRO) POWDER FERMENTED WASTE AT DIFFERENT TIMES - Muhammad Rizky Anwar; Dini Julia Sari Siregar (Journal of Innovation Research and Knowledge, 2025)
The aim of this research is to determine the best storage time for the fermentation process for the content of cyanide acid (HCN), crude protein and gross energy in fermented winprob (otw_pro) onggok in powder form. The hypothesis of this research is that the best storage time for the fermentation process can reduce and increase the content of cyanide acid (HCN) and increase crude protein and gross energy in fermented winprob (otw_pro) onggok in powder form. The materials used in the research were onggok, winprob (powder form) and molasses. Materials for chemical feed nutritional tests are H2SO4, NaOH, Acetone, Boric acid HCl and methyl red indicator. The tools used are plastic jars, buckets, knives, and scales. The tools used in nutritional chemistry tests are calorie meter bombs, thermometers, digestion tools, distillation tools, titration tools, and shoxlet tools. The research method used in the research was a non-factorial Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatments given were as follows: LP0: storage time 0 days (control), LP 1: storage time 1 week, LP2: storage time 2 weeks, LP3: storage time 3 weeks, and LP4: storage time 4 weeks. The parameters observed in this research were analysis of the content of cyanide acid (HCN), crude protein and gross energy in Winprob (otw_pro) fermented onggok in powder form. Proximate testing is carried out in the laboratory. The conclusion of this research is that onggok fermented with Win Prob probiotics in powder form with a storage period of 3 weeks is the best treatment which can reduce cyanide acid (HCN) content and increase crude protein and gross energy.